Effectiveness and Safety of Short‐stay Units in the Emergency Department: A Systematic Review. (22nd July 2015) - Galipeau, James; Pussegoda, Kusala; Stevens, Adrienne; Brehaut, Jamie C.; Curran, Janet; Forster, Alan J.; Tierney, Michael; Kwok, Edmund S. H.; Worthington, James R.; Campbell, Samuel G.; Moher, David; Zehtabchi, Shahriar
Abstract Objectives Overcrowding is a serious and ongoing challenge in Canadian hospital emergency departments (EDs) that has been shown to have negative consequences for patient outcomes. The American College of Emergency Physicians recommends observation/short‐stay units as a possible solution to alleviate this problem. However, the most recent systematic review assessing short‐stay units shows that there is limited synthesized evidence to support this recommendation; it is over a decade old and has important methodologic limitations. The aim of this study was to conduct a more methodologically rigorous systematic review to update the evidence on the effectiveness and safety of short‐stay units, compared with usual care, on hospital and patient outcomes. Methods A literature search was conducted using MEDLINE, the Cochrane Library, Embase, ABI/INFOM, and EconLit databases and gray literature sources. Randomized controlled trials of ED short‐stay units (stay of 72 hours or less) were compared with usual care (i.e., not provided in a short‐stay unit), for adult patients. Risk‐of‐bias assessments were conducted. Important decision‐making (gradable) outcomes were patient outcomes, quality of care, utilization of and access to services, resource use, health system–related outcomes, economic outcomes, and adverse events. Results Ten reports of five studies were included, all of which compared short‐stay units with inpatient care. Studies had small sample sizes and were collectively at a moderate risk of bias. Most outcomes were only reported by one study and the remaining outcomes were reported by two to four studies. No deaths were reported. Three of the four included studies reporting length of stay found a significant reduction among short‐stay unit patients, and one of the two studies reporting readmission rates found a significantly lower rate for short‐stay unit patients. All four economic evaluations indicated that short‐stay units were a cost‐saving intervention compared to inpatient care from both hospital and health care system perspectives. Results were mixed for outcomes related to quality of care and patient satisfaction. Conclusions Insufficient evidence exists to make conclusions regarding the effectiveness and safety of short‐stay units, compared with inpatient care.